Effect and mechanism of siderite on reverse anionic flotation of quartz from hematite - Luo, Xi-mei; Yin, Wan-zhong; Wang, Yun-fan; Sun, Chuan-yao; Ma, Ying-qiang; Liu, Jian (Journal of Central South University, 2016)
Reverse flotation technology is one of the most efficient ways to improve the quality and reduce impurity of iron concentrate. Mineral processors dealing with hematite face a challenge that the flotation results of reverse flotation of hematite are poor in presence of siderite using fatty acid as collector, starch as depressant of iron minerals and calcium ion as activator of quartz at strong alkaline pH. In this work, the effect of siderite on reverse anionic flotation of quartz from hematite was investigated. The effect mechanism of siderite on reverse flotation of hematite was studied by solution chemistry, ultraviolet spectrophotometry (UV) and Fourier transform infrared spectroscopy (FTIR). It was observed that siderite had strong depressive effect on quartz in flotation using sodium oleate as collector, corn starch as depressant of iron minerals and calcium chloride as activator of quartz at strong alkaline pH. The starch was adsorbed onto calcium carbonate by chemical reaction which was formed by CO 3 2- from siderite dissolution and Ca 2+ from calcium chloride as activator of quartz and precipitated on the surface of quartz, which resulted in improving the hydrophilic ability of quartz.